STUDY OF URSODEOXYCHOLIC ACID INFLUENCE ON EFFICACY AND SAFETY OF STATIN THERAPY IN PATIENTS WITH DISEASES OF THE LIVER, GALL BLADDER AND/OR BILIARY TRACT (THE RAKURS STUDY) - S. Yu. Martsevich; N. P. Kutishenko; L. Yu. Drozdova; O. V. Lerman; V. A. Nevzorova; I. I. Reznik; G. V. Shavkuta; D. A. Yahontov (Столичная издательская компания, 2015)
Aim. To assess the potential of ursodeoxycholic acid (UDCA) in the prevention of liver dysfunction in patients with cardiovascular diseases (CVD) and high risk of cardiovascular events (CVE) with indications for statins use. Material and methods. Patients (n=262, age 60.1±8.9 years) took statins for secondary prevention of CVE in observational cohort study. The follow-up duration was 6 months. UDCA was recommended for all patients because of liver diseases and/or biliary tract. Some of the patients with high treatment compliance strictly followed recommendations to take UDCA, and another part of the patients with low treatment compliance did not take UDCA. Comparison of these groups allowed highlighting UDCA effects. Results. Controlled lipid-lowering therapy in combination with UDCA resulted in a significant reduction in total cholesterol (TC) and low density lipoprotein cholesterol levels after 6 months of follow-up to 4.3 mmol/L and 2.3 mmol/L, respectively (p<0.001). Deterioration in the dynamics of alanine-aminotransferase (ALT), aspartate aminotransferase (AST), creatinphosphokinase (CPK) and gamma glutamine transferase (GGT), as well as increase in serum bilirubin was not found. Moreover, in general significant decrease in ALT, AST, GGT and alkaline phosphatase (p<0.001) was observed, the levels of total serum bilirubin and CPK did not change at the end of the study (p=0.65 and p=0.16, respectively). Taking UDCA simultaneously with statins led to additional reduction in TC and low density cholesterol compared with statin monotherapy (p=0.01). Conclusion. One of the affordable and effective ways to deal with a wider statin use in patients with liver and biliary tract disorders is their co-administration with UDCA.